Newts can normalize duplicated proximal–distal disorder during limb regeneration. Issue 12 (22nd November 2018) - Koriyama, Kazuki; Sakagami, Risa; Myouga, Ayumi; Hayashi, Toshinori; Takeuchi, Takashi
Abstract : Background: Urodele animals can regenerate their limbs from the blastemas. The previous results of grafting proximal blastemas to distal limb levels (P to D transplantation) led to serial duplication of limb segments. However, it is unknown whether grafting to any distal levels in P to D transplantation causes serial duplication. In other words, it is unknown whether or not newt limbs can normalize such a kind of duplicated type of positional disorder in the proximal–distal axis. Therefore, we grafted the most proximal blastemas to various distal levels of the proximal–distal axis using newts ( Pleurodeles waltl ). The transgenic newts expressing green fluorescent protein or mCherry were used to clearly distinguish between donor and host tissues.Results : Normal segmental formation without duplication occurred in P to D transplantation within the stylopod. In addition, donor blastemas lost the fates of the stylopods, and the missing portion in the stylopod by amputation was restored by the insertion of host cells. In contrast, the blastemas from the stylopod formed whole limbs after transplantation to the tail.Conclusions : These results showed that urodele limbs can normalize the duplicated type of positional disorder within the stylopod by erasing a part of the fate in the blastemas. Developmental Dynamics 247:1276–1285, 2018. © 2018 Wiley Periodicals, Inc. Key Findings: Normal segmental formation without duplication occurred in grafting proximal blastemas to distal limb levels within the stylopod. Donor blastemas lost the fates of the stylopods. Urodele limbs can normalize the duplicated type of positional disorder within the stylopod by erasing a part of the fate in the blastemas.